Improvement Of Led Light Extraction Efficiency By Silica Micro Repeating Structure Growth - Joshua Gan, Oon Joo (2018)
Light extraction efficiency (LEE) is an important factor for Light Emitting Diodes (LED). As of today, most LEE improvement methods involve complex fabrication either on the finished LED chip or during the LED processing itself. In this study, micro repeating structures (MRS) are constructed using silica micro repeating structure growth (SMRSG) to improve LEE. In contrast to other complex fabrication methods, the SMRSG was done through a Stöber solution growth method. The solution preparation was relatively simple, using tetraethyl orthosilicate (TEOS), surfactant and solvents. The LEE result of the LED after SMRSG was characterized through using a spectrophotometer. It showed an average of 0.77% increment in brightness for unroughened LED. A separate study on using sodium hydroxide (NaOH) for post LED fabrication cleaning was also conducted. A new discovery was achieved where the brightness of the LED was increased by 5.05% and 1.11% for roughened and unroughened LED respectively. The short cleaning time (30 seconds) with NaOH was to clean the LED surface from contaminants. This suggests that the presence of the SMRSG which is an MRS and cleaning of the LED surface was able to change the LEE of the LED.